Home-based parental involvement amongst Pakistani families in Hong Kong. Issue 2 (2nd April 2020) - Chee, Wai-Chi; Ullah, Rizwan
ABSTRACT: Ethnic minority parents often appear to be less involved in school functions and activities than their culturally dominant counterparts. Their invisibility is usually assumed due to a lack of either interest or parental capacity to oversee their children's education. However, the simplistic equation between parental involvement in children's education and their participation in school is largely informed by middle-class cultural norms that ignore diversity. Data drawn from home visits and in-depth, semi-structured interviews amongst Pakistani parents and children in Hong Kong reveals that the involvement of these parents only seems less visible because it is largely based at home rather than in schools. The parental involvement of this ethnic minority is influenced by socio-economic and cultural factors that separate school from home, divide parental responsibilities by gender, and set expectations for children with primary reference to the parents' own experiences. These research findings on how such characteristics shape the outcomes of parental involvement can inform school practices to build more effective home-school collaboration and enhance children's academic achievement.